Morpho-Anatomy and Ontogeny of the Floral Nectaries of Cardiospermum grandiflorum and Urvillea chacoensis (Sapindaceae) - Solis, Stella Maris (2009)
The morphology, anatomy and ontogeny the floral nectaries of two species of Sapindaceae (Paullinieae), viz. Cardiospermum grandiflorum and Urvillea chacoensis, were studied using light and scanning electron microscopy. Both species are monoecious with oblique monosymmetric flowers. The floral nectaries are located at the base of the androgynophore. Vascular tissue supplying the nectaries consists of phloem. Cardiospermum grandiflorum has a posterior nectary with two lobes without any specially differentiated tissue, and with nectarostomata. In Urvillea chacoensis the nectary has four lobes; two posterior ones with distinctive nectariferous tissue with nectarostomata on the abaxial side, and two minor anterior ones that are histologically similar but lack nectarostomata. The nectaries in both species have a common base with the petals. Since the nectaries are macroscopically differentiated they are considered as structural nectaries.